SECONDARY METABOLITES OF THE FUNGUS TRICHOLOMA CALIGATUM (Web of Teachers: Inderscience Research, 2025)
In recent years, the demand for health care and food products has been on the rise. Mushrooms are gaining traction in an important product not only of the food industry, but also of the medical sector. Ancient and important fungus Tricholoma caligatum has long been used by humans as a medicinal substance. It presents various medicinal properties such as anti-cancer, immune boosting and antioxidant effects. In addition, it is considered a wholesome and healthy food product all over the world. A large number of secondary metabolites are distinguished from the Tricholoma species. It contains a number of terpenoids, alkaloids and steroids containing these secondary metabolites. This fungus is mainly known in Europe as Tricholoma matsutake. There are many different versions of this fungus. The distribution of the secondary metabolites of each version is different, as these vary with ecology and climate change. The changes can sometimes also be seen in the difference in smell and taste. In short, the Tricholoma caligatum group is in need of significant modern study and revision.